The Role of Leadership Style in Moderating Quality of Work Life and Emotional Labor on Employee Performance - I Putu Darmawan; Ida Ayu Putu Widani Sugianingrat; I Made Astrama (UNHI Press, 2024)
Purpose - This research aims to analyze the role of quality of work life, and emotional labor which is moderated by leadership style on the performance of employees of private religious colleges in Bali. Methodology - The location of this research includes three private university campuses with Hindu religious nuances in Bali. The sampling method in this research was a saturated sample, namely all employees at Private Hindu Religious Universities in Bali Province, totaling 100 people. The analytical method used is partial least square (PLS) with structural equation modeling (SEM). Finding - The results of the research show that quality of work life has a significant influence on employee performance, emotional labor has a significant influence on employee performance, Leadership style does not play a role in moderating the influence of quality of life work on employee performance and leadership style do not play a role in moderating the influence of emotional labor on employee performance.